Peran Ilmu Pengetahuan Dalam Mewujudkan Kehidupan Mulia: Perspektif Islam, Pemikiran Ibnu Qayyim Dan Al-Ghazali, Serta Implikasinya Dalam Kehidupan Dunia Dan Akhirat - Devi Aprilia Rachmawati; Ainur Rofiq Sofa; Muhammad Sugianto (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study examines the role of knowledge in shaping a noble life from the Islamic perspective, referencing the thoughts of prominent figures such as Ibn Qayyim and Al-Ghazali. The study shows that in Islam, knowledge serves not only as worldly knowledge but also as a means to draw closer to Allah and enhance the quality of life, both in this world and the hereafter. Ibn Qayyim emphasizes that beneficial knowledge helps individuals understand the essence of life and the purpose of creation, while Al-Ghazali highlights that knowledge functions as a purifier of the soul and a spiritual foundation. Furthermore, knowledge acts as a unifier of both the worldly and the spiritual, and as a key to forming noble character and morals. This research also reveals that knowledge has a positive impact on society, creating social harmony and contributing to collective well-being. Overall, the findings emphasize that knowledge in Islam, through the thoughts of Ibn Qayyim and Al-Ghazali, is the key to achieving a balanced, blessed life that aligns with Islamic principles.